IMPLEMENTASI KEBIJAKAN SISTEM KENAIKAN PANGKAT TANPA BERKAS DI BADAN KEPEGAWAIAN DAERAH PROVINSI JAWA TENGAH - Candra Pradipta; Yuwanto .; Wachid Abdulrahman (Journal of Politic and Government Studies, 2016)
This research aims to know the implementation of the system policy file without promotion and driving factor as well as a barrier in the implementation of the system policy file without promotion in the BKD of Central Java. The current Government of many utilize the internet in order to better provide services effectively and efficiently, one of which is the promotion of service performed in the province of Central Java. The application utilizes in practice, it is very exciting to be examined because it is a new thing and in the effective value. This type of research is descriptive qualitative data collection techniques with techniques of observation, i.e. the research done by doing a direct observation of the subject as well as in-depth interviews with interviews as well as being supported by primary and secondary data obtained during the research. The subject of research is the BKD Of Central Java. From the results of research show that the system policy file without any promotion is a new policy that provides convenience for civil servants in management of the promotion, due to the system of CIVIL SERVANTS (PNS) no longer need to bother in taking care of the file promotion because all of the files have been uploaded and only stayed there proposed. In addition it is also time saving, faster, as well as facilitate PNS as the object that was awarded the promotion. Then to pendorongnya factor is the availability of human resources, budget, as well as ancillary equipment such as computers and the internet. Penghambatnya factor is the lack of awareness of PNS to supplement and update the information personnel. A summary of this research is that the promotion without file does not completely without a file because the PNS still prompted for the file. Important advice is a must the existence of database repair of PNS so that the ease in implementation. Keywords: Policy Implementation, Promotion, Without Files, BKD